DEVELOPING ENGLISH MATERIALS OF MIDWIFERY STUDENTS AT STIKES SUKMA WIJAYA SAMPANG - Ika meilinda Ummul ma'rufa (Surakarta English and Literature Journal, 2023)
ABSTRACT The demand of qualified midwives in their job field encourages the midwifery academy include English language as the compulsory subject for the students. It is very rare to find the ESP books designed for the students of midwifery. This study is aimed at developing an English material which is specified to the students of Midwifery Academy of Sukma Wijaya Sampang. It was carried out to require the students’ need and interest. It was conducted by using the Research and Development (R & D) design in which the procedures of need assessment, and expert validation were included. The data collection involved a number of instruments, namely questionnaires, interviews, and observation. The questionnaires were applied to the students, and chief of midwifery department on the procedure of need assessment, while the checklist was given to the experts on the process of product validation. All the data were analyzed descriptively and could be concluded that the material was applicable for the students in terms of their attractiveness and appropriateness of the content and level of the difficulty.